A case of grade I rectal prolapse in a calf with congenital tail defect - Tijjani, Abdulnasir; Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Adamu, Lawan; Abba, Yusuf; Sadiq, Muhammad Abubakar; Mohammed, Konto; Mohd Lila, Mohd Azmi; Haron, Abdul Wahid (International Organization of Scientific Research, 2015)
Rectal prolapse is a condition involving displacement of the rectum, commonly due to excessive straining, diet or inherited traits. A 6-month-old calf with congenital tail defect weighing 68 kg was presented to the University Veterinary Hospital, Universiti Putra Malaysia with a grade I incomplete rectal prolapse. This condition was corrected with surgical repair using Buhner's needle and umbilical tape following epidural nerve blocking using 2% Lidocaine. The calf was also treated with the administered 650ml of 0.9% Nacl intravenous fluid and 100ml of calcium borogluconate intravenously. Topical wound healing powder Negasunt containing (Sulphanilamide 5.0% w/w, coumaphos 3.0% w/w, propoxur 2.0% w/w) and povidone iodine was applied topically to prevent maggots and secondary infection. Norodine (trimethoprim sulfadiazine) antibiotic was administered at dose rate of 0.15mg/kg SID for two days.Prompt surgical intervention and treatment resolved the condition in the calf.